Upaya Kepala Sekolah Dalam Menanamkan Nilai-Nilai Karakter Peserta Didik SMP Negeri 6 Kabupaten Kaur Provinsi Bengkulu - Maryani, Histi; Danim, Sudarwan; Somantri , Manap (Manajer Pendididikan, 2024)
This research aims to describe the school principal's efforts to embeded character values in students at State Junior High School 6 Kaur district. Research uses qualitative descriptive methods. Research subjects were the principal, deputy principal, teachers and students at State Junior High School 6 Kaur district. Research data was obtained from interviews, observation and documentation. Research data analysis includes data reduction, data presentation, verification and drawing conclusions. The result of research  show that the school principal's efforts in embeded character values in students at State Junior High School 6 Kaur district have a significant role in shaping student character. The school principal is actively involved in designing and implementing programs aimed at developing moral values and positive behavior in the school environment.